Trap and ambush therapy using sequential primary and tumor escape-selective oncolytic viruses - Mason J. Webb; Timothy Kottke; Benjamin L. Kendall; Jack Swanson; Chisom Uzendu; Jason Tonne; Jill Thompson; Muriel Metko; Madelyn Moore; Mitesh Borad; Lewis Roberts; Rosa M. Diaz; et al. (Molecular Therapy: Oncolytics, 2023)
In multiple models of oncolytic virotherapy, it is common to see an early anti-tumor response followed by recurrence. We have previously shown that frontline treatment with oncolytic VSV-IFN-β induces APOBEC proteins, promoting the selection of specific mutations that allow tumor escape. Of these mutations in B16 melanoma escape (ESC) cells, a C-T point mutation in the cold shock domain-containing E1 (CSDE1) gene was present at the highest frequency, which could be used to ambush ESC cells by vaccination with the mutant CSDE1 expressed within the virus. Here, we show that the evolution of viral ESC tumor cells harboring the escape-promoting CSDE1C-T mutation can also be exploited by a virological ambush. By sequential delivery of two oncolytic VSVs in vivo, tumors which would otherwise escape VSV-IFN-β oncolytic virotherapy could be cured. This also facilitated the priming of anti-tumor T cell responses, which could be further exploited using immune checkpoint blockade with the CD200 activation receptor ligand (CD200AR-L) peptide. Our findings here are significant in that they offer the possibility to develop oncolytic viruses as highly specific, escape-targeting viro-immunotherapeutic agents to be used in conjunction with recurrence of tumors following multiple different types of frontline cancer therapies.